Jewish women on stage, film, and television - Mock, Roberta (Palgrave Macmillan, 2007)
This title exposes and traces a previously unrecognized performance tradition on extraordinary Jewish women in the Diaspora, from Rachel and Sarah Bernhardt in 19th century France to Roseanne and Sandra Bernhard in late 20th century America.
Includes bibliographical references and index
Introduction: Performing the Jewess -- pt. 1. La belle juive. Jewess-ence: woman and disease -- Celebrity and consumption -- pt. 2. Spectacular American bodies. Big Jewish mamas -- Jewing up -- pt. 3. "Fuck 'em if they can't take a joke!" -- Mimicking whiteness
Keywords: Geschichte 1800-2000; Jewish actors; Jewish women in motion pictures; Jewish women; Actresses; Schauspielerin; Jüdin